DNA methylation biomarkers and myopia - Dong, Xing Xuan (2024)
Funding Information: This study was supported by the National Natural Science Foundation of China (82122059) and the National Key R&D Program of China (2021YFC2702100, 2021YFC2702103, and 2021YFC2702104). Publisher Copyright: © The Author(s) 2024.